Strategies to improve recruitment to multicomponent group programs for overweight and obesity: a systematic review - Inanna Reinsperger; Sarah Wolf; Ingrid Zechmeister-Koss (Frontiers in Health Services)
ObjectiveMulticomponent programs are recommended for the treatment of children, adolescents, and adults with overweight or obesity. However, program providers often face difficulties reaching their target groups. This systematic review aimed at identifying recruitment strategies for multicomponent overweight and obesity programs in group settings and at summarizing barriers and facilitators for participation.MethodsWe searched electronic databases (MEDLINE, CINAHL, The Cochrane Library, PsycInfo, Web of Science) and included primary studies reporting on recruitment strategies for multicomponent group programs for children, adolescents, and adults with overweight or obesity. All study designs were eligible for inclusion. Study characteristics, recruitment strategies as well as barriers and facilitators were extracted from the included articles, summarized in a table format, and synthesized narratively.ResultsOf the 1,082 articles identified through the systematic literature search, 16 studies met the inclusion criteria and were included in the analysis. Eleven focused on children and adolescents, and five on adults. Recruitment strategies were categorized into active (e.g., referral by health professionals, direct contact) and passive methods (e.g., media advertising, flyers, posters). In most studies, a combination of several active and passive methods was applied or recommended. For socioeconomically disadvantaged groups, some targeted strategies were identified, e.g., recruitment in specific locations or through trained peers. Several possible barriers to recruitment were mentioned in the included studies, e.g., stigmatization, lack of time and resources of the healthcare staff, organizational barriers, lack of motivation of potential participants.ConclusionThis systematic review identified several active and passive strategies for recruiting children, adolescents, and adults with overweight and obesity into multicomponent group programs. The overview of possible recruitment methods is a valuable decision support to be used by program providers when designing new or adapting existing programs.